Aberrant Expression and Oncogenic Activity of SPP1 in Hodgkin Lymphoma - Stefan Nagel; Corinna Meyer (Biomedicines)
Background: Hodgkin lymphoma (HL) is a B-cell-derived malignancy and one of the most frequent types of lymphoma. The tumour cells typically exhibit multiple genomic alterations together with aberrantly activated signalling pathways, driven by paracrine and/or autocrine modes. SPP1 (alias osteopontin) is a cytokine acting as a signalling activator and has been connected with relapse in HL patients. To understand its pathogenic role, here, we investigated the mechanisms and function of deregulated SPP1 in HL. Methods: We screened public patient datasets and cell lines for aberrant SPP1 expression. HL cell lines were stimulated with SPP1 and subjected to siRNA-mediated knockdown. Gene and protein activities were analyzed by RQ-PCR, ELISA, Western blot, and immuno-cytology. Results: SPP1 expression was detected in 8.3% of classic HL patients and in HL cell line SUP-HD1, chosen to serve as an experimental model. The gene encoding SPP1 is located at chromosomal position 4q22 and is genomically amplified in SUP-HD1. Transcription factor binding site analysis revealed TALE and HOX factors as potential regulators. Consistent with this finding, we showed that aberrantly expressed PBX1 and HOXB9 mediate the transcriptional activation of SPP1. RNA-seq data and knockdown experiments indicated that SPP1 signals via integrin ITGB1 in SUP-HD1. Accordingly, SPP1 activated NFkB in addition to MAPK/ERK which in turn mediated the nuclear import of ETS2, activating oncogenic JUNB expression. Conclusions: SPP1 is aberrantly activated in HL cell line SUP-HD1 via genomic copy number gain and by homeodomain transcription factors PBX1 and HOXB9. SPP1-activated NFkB and MAPK merit further investigation as potential therapeutic targets in affected HL patients.